Measurement of Malrotation on Direct Radiography in Pediatric Distal Radius Fractures: Prospective Observational Study. Issue 18 (May 2016) - Duymus, Tahir Mutlu; Mutlu, Serhat; Komur, Baran; Mutlu, Harun; Yucel, Bulent; Parmaksizoglu, Atilla Sancar
Abstract : Abstract: The aim of this prospective study was to test a mathematical method of measuring the malrotation of pediatric distal radius fractures (PDRFs) from direct radiographs. A total of 70 pediatric patients who presented at the Emergency Department with a distal radius fracture were evaluated. For 38 selected patients conservative treatment for PDRF was planned. Anteroposterior and lateral radiographs were taken of all of the patients for comparison before and after reduction. Radius bone diameters were measured in the coronal and sagittal planes on the healthy and fractured sides. Using the diameter values on the healthy side and the new diameter values on the fractured side in the rotation formula, the degree of malrotation between the fracture ends was calculated. The mean follow-up period was 13.5 months. Patients' mean age was 10.00 ± 3.19 years (range, 4–12 years). The rotation degree in the sagittal plane significantly differed between the proximal (26.52°±2.84°) and distal fracture ends (20.96°±2.73°) ( P = 0.001). The rotation degree in the coronal plane significantly differed between the proximal (26.70°±2.38°) and distal fracture ends (20.26°±2.86°) ( P = 0.001). The net rotation deformity of the fracture line was determined to be 5.55°± 3.54° on lateral radiographs and 5.44°± 3.35° on anteroposterior radiographs, no significant difference was observed between measurements ( P >0.05). The malrotation deformity in PDRF occurs with greater rotation in the proximal fragment than in the distal fragment. The net rotation deformity created between the fracture ends can be calculated on direct radiographs. Level of Evidence: Diagnostic, Level II